Phenotyping of idiopathic pulmonary arterial hypertension: a registry analysis - Höper, Marius; Dwivedi, Krit; Pausch, Christine; Lewis, Robert A; Olsson, Karen Maria; Huscher, Doerte; Pittrow, David; Grünig, Ekkehard; Stähler, Gerd; Vizza, Carmine Dario; Gall, Henning; Distler, Oliver; et al. (The lancet. Respiratory medicine, 2022)
Background - Among patients meeting diagnostic criteria for idiopathic pulmonary arterial hypertension (IPAH), there is an emerging lung phenotype characterised by a low diffusion capacity for carbon monoxide (DLCO) and a smoking history. The present study aimed at a detailed characterisation of these patients. - Methods - We analysed data from two European pulmonary hypertension registries, COMPERA (launched in 2007) and ASPIRE (from 2001 onwards), to identify patients diagnosed with IPAH and a lung phenotype defined by a DLCO of less than 45% predicted and a smoking history. We compared patient characteristics, response to therapy, and survival of these patients to patients with classical IPAH (defined by the absence of cardiopulmonary comorbidities and a DLCO of 45% or more predicted) and patients with pulmonary hypertension due to lung disease (group 3 pulmonary hypertension). - Findings - The analysis included 128 (COMPERA) and 185 (ASPIRE) patients with classical IPAH, 268 (COMPERA) and 139 (ASPIRE) patients with IPAH and a lung phenotype, and 910 (COMPERA) and 375 (ASPIRE) patients with pulmonary hypertension due to lung disease. Most patients with IPAH and a lung phenotype had normal or near normal spirometry, a severe reduction in DLCO, with the majority having no or a mild degree of parenchymal lung involvement on chest computed tomography. Patients with IPAH and a lung phenotype (median age, 72 years [IQR 65-78] in COMPERA and 71 years [65-76] in ASPIRE) and patients with group 3 pulmonary hypertension (median age 71 years [65-77] in COMPERA and 69 years [63-74] in ASPIRE) were older than those with classical IPAH (median age, 45 years [32-60] in COMPERA and 52 years [38-64] in ASPIRE; p<0·0001 for IPAH with a lung phenotype vs classical IPAH in both registries). While 99 (77%) patients in COMPERA and 133 (72%) patients in ASPIRE with classical IPAH were female, there was a lower proportion of female patients in the IPAH and a lung phenotype cohort (95 [35%] COMPERA; 75 [54%] ASPIRE), which was similar to group 3 pulmonary hypertension (336 [37%] COMPERA; 148 [39%] ASPIRE]). Response to pulmonary arterial hypertension therapies at first follow-up was available from COMPERA. Improvements in WHO functional class were observed in 54% of patients with classical IPAH, 26% of patients with IPAH with a lung phenotype, and 22% of patients with group 3 pulmonary hypertension (p<0·0001 for classical IPAH vs IPAH and a lung phenotype, and p=0·194 for IPAH and a lung phenotype vs group 3 pulmonary hypertension); median improvements in 6 min walking distance were 63 m, 25 m, and 23 m for these cohorts respectively (p=0·0015 for classical IPAH vs IPAH and a lung phenotype, and p=0·64 for IPAH and a lung phenotype vs group 3 pulmonary hypertension), and median reductions in N-terminal-pro-brain-natriuretic-peptide were 58%, 27%, and 16% respectively (p=0·0043 for classical IPAH vs IPAH and a lung phenotype, and p=0·14 for IPAH and a lung phenotype vs group 3 pulmonary hypertension). In both registries, survival of patients with IPAH and a lung phenotype (1 year, 89% in COMPERA and 79% in ASPIRE; 5 years, 31% in COMPERA and 21% in ASPIRE) and group 3 pulmonary hypertension (1 year, 78% in COMPERA and 64% in ASPIRE; 5 years, 26% in COMPERA and 18% in ASPIRE) was worse than survival of patients with classical IPAH (1 year, 95% in COMPERA and 98% in ASPIRE; 5 years, 84% in COMPERA and 80% in ASPIRE; p<0·0001 for IPAH with a lung phenotype vs classical IPAH in both registries). - Interpretation - A cohort of patients meeting diagnostic criteria for IPAH with a distinct, presumably smoking-related form of pulmonary hypertension accompanied by a low DLCO, resemble patients with pulmonary hypertension due to lung disease rather than classical IPAH. These observations have pathogenetic, diagnostic, and therapeutic implications, which require further exploration. - Funding - COMPERA is funded by unrestricted grants from Acceleron, Bayer, GlaxoSmithKline, Janssen, and OMT. The ASPIRE Registry is supported by Sheffield Teaching Hospitals NHS Foundation Trust, Sheffield, UK.
Gesehen am 22.05.2023
Available online 28 June 2022, Version of Record 27 September 2022